Stress Reduction Factor for Unsupported Lengths - Roy, Ranjit (Engineering Journal, 1981)
The AISC Specification allows Fb = 0.66Fy for structural shapes meeting the compact criteria of Sect. 1.5.1.4.1, when loaded in the plane of their minor axis. A reduced bending stress, Fb = 0.6Fy, is allowed for shapes failing to meet the compactness criteria. The above allowable values require that the compression flange be braced at a maximum interval of lengths as determined by the smaller value obtained from the expressions described in this paper.